A case study approach into leadership strategy and practice at Valebow Academy. - Levien, Samuel (2017)
This study investigates the effectiveness of leadership at Valebow Academy; in particular, the focus is on the model of distributed leadership which has recently been implemented by the new leadership team. It assesses the impact of this new strategy, focussing on cultural differences and perspectives of change management by long term teachers. There is identification of the particular context of the school and measurement of the outcome of such radical changes in the leadership style. The aim of this dissertation is not to understand the model of distributed leadership in itself and evaluate to what extent this is being used. The hypotheses is that the introduction of a new leadership style has led to a more positive perception by teachers of leadership at all levels of the school. Previous studies indicate there are some key positives and potential negatives in the application of the distributed leadership model and the literature review highlights how the theory surrounding this concept is relatively new, therefore focuses on how perspectives on this theory has developed and changed, becoming more concrete due to growing evidence of its use in everyday practice. The research suggests that distributed leadership is still in its formation stages, so it is still relatively abstract in its meaning, implying that there can be many ways of putting it into practice, in both a formal and informal manner. The literature analysis also considers theoretical cultural differences between both Mexican and British cultures and how this could have an impact on perceptions towards a distributed leadership model. 4 To date, there has not been any academic research done on leadership within this school. One of the purposes of this study is to attempt to clarify whether there is any significant theory, practice divide and observe whether this has had an impact on the leadership at Valebow Academy. It examines how distributed leadership has been used to overcome lingering issues of a distinct, exclusive hierarchy. The research indicates that there has been a positive effect of the change in perceptions of leadership in the school. As the literature explored, it shows some aspects of cultural differences in the viewpoint of Mexican and British perspectives. The suggested effects of the leadership change are that of expanded growth and professional development, as well as a growing culture of feeling able to approach members of leadership without being worried about showing weakness. The study also reveals the impact, at the times the lack of communication between and from leaders, which has effects on a wide range of areas of the school. There is suggestion of further study into the varying results of teachers who had been at the school for different lengths of time. I also recommend wider studies on the effect of distributed leadership in international schools within Mexico to further understand different cultural perceptions of leadership.